Relationship between employability and turnover intention: The moderating effects of organizational support and career orientation. (March 2020) - Baranchenko, Yevhen; Xie, Yizhong; Lin, Zhibin; Lau, Marco Chi Keung; Ma, Jie
Abstract: This study examines the impact of employability on turnover intention by differentiating internal and external employability, and considering the possible moderating roles of perceived organizational support (POS) and career orientation. Using a sample of 411 responses to a two-wave questionnaire survey generated from six cities in China, we find that external employability positively influenced turnover intention, but internal employability negatively influenced turnover intention. The results also indicate that POS had a positive moderating effect only on the relationship between external employability and turnover intention. Furthermore, for employees with disengaged career orientation, external employability exerts a strong impact on turnover intention. This study adds to the limited research empirically linking employability and turnover intention, whereas the findings can be used by HRM practitioners to factor in organizational support and career orientation initiatives that improve the retention of employees with high external employability.